Human Resource Strategy Development in Facing Challenges Digital Transformation: Case Study of PT Telkom Indonesia - Gifa, Naufal Zaka Putra; Rizke, Muhammad Bintang; Sari, Susanti Ratna; Rahmawati, Nur Diana; Yofianka, Farah Febrina; Tsaniyah, Faizah Ats; Ayu, Siti Ajeng; N, Rusdi Hidayat; Ikaningtyas , Maharani (Jurnal Bisnis dan Komunikasi Digital, 2025)
Digital transformation is a strategic challenge for PT Telkom Indonesia in the midst of global technological disruption. This study aims to evaluate the human resource (HR) development strategy implemented by the company in supporting the transformation process. Through the literature study method, this research highlights various approaches taken by Telkom, such as strengthening digital competencies through Telkom Corporate University, implementing a digital work culture, developing digital leadership, and adaptive and sustainable talent management. However, the implementation of these strategies faces various challenges, including intergenerational competency gaps, resistance to change, and limited training budgets. The results of the study provide a comprehensive overview of the importance of integration between technology and HR readiness in facing digital transformation, and offer best practices for the SOE sector and other industries.